January first : a child's descent into madness and her father's struggle to save her - Schofield, Michael, 1976- (New York : Crown Publishers, 2012)
This work is an account of a father's fight to save his child from an extremely severe case of mental illness in the face of overwhelming adversity. The creator of the janisjourney.org blog traces the story of his fight to save his daughter from her severe schizophrenia and what he has learned about mental illness and its impact on family life.
Keywords: Schofield, January, -- 2002-; Schizophrenia in children -- Patients -- Biography; Schizophrenics -- Family relationships